Feasibility of membrane ultrafiltration as a single-step clarification and fractionation of microalgal protein hydrolysates - Soto-Sierra, Laura; Nikolov, Zivko L. (Frontiers in Bioengineering and Biotechnology, 2022)
Protein hydrolysates are one of the most valuable products that can be obtained from lipid-extracted microalgae (LEA). The advantages of protein hydrolysates over other protein products encompass enhanced solubility, digestibility, and potential bioactivity. The development of an economically feasible process to produce protein hydrolysates depends on maximizing the recovery of hydrolyzed native protein from the lipid-extracted algal biomass and subsequent fractionation of hydrolyzed protein slurry. Previously, we reported a method for fractionation of enzymatically generated protein hydrolysates by acidic precipitation of algal cell debris and unhydrolyzed protein, precipitate wash, centrifugation, and depth filtration. The present study evaluates tangential flow ultrafiltration as a single-step alternative to centrifugation, precipitate wash, and depth filtration. The results demonstrate that the tangential flow ultrafiltration process has a potential that deserves further investigation. First, the membrane diafiltration process uses a single and easily scalable unit operation (tangential flow filtration) to separate and “wash out” hydrolyzed protein from the algal residue. Second, the protein recovery yield achieved with the tangential flow process was >70% compared to 64% previously achieved by centrifugation and depth filtration methods. Finally, protein hydrolysates obtained by membrane ultrafiltration exhibited slightly better heat and pH stability.